Control theory for partial differential equations : continuous and approximation theories - Lasiecka, I.; Triggiani, R. (Cambridge : Cambridge University Press, 2000)
Originally published in 2000, this is the first volume of a comprehensive two-volume treatment of quadratic optimal control theory for partial differential equations over a finite or infinite time horizon, and related differential (integral) and algebraic Riccati equations. Both continuous theory and numerical approximation theory are included. The authors use an abstract space, operator theoretic approach, which is based on semigroups methods, and which is unifying across a few basic classes of evolution. The various abstract frameworks are motivated by, and ultimately directed to, partial differential equations with boundary/point control. Volume 1 includes the abstract parabolic theory for the finite and infinite cases and corresponding PDE illustrations as well as various abstract hyperbolic settings in the finite case. It presents numerous fascinating results. These volumes will appeal to graduate students and researchers in pure and applied mathematics and theoretical engineering with an interest in optimal control problems.
I. Abstract parabolic systems -- II. Abstract hyperbolic-like systems over a finite time horizon.
Includes bibliographical references and index.
Keywords: Differential equations, Partial; Control theory; Dynamical Systems